2019
DOI: 10.18632/aging.102521
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially expressed genes in non-small cell lung cancer

Abstract: Lung cancer is the most common malignant tumor and the leading cause of cancer-related deaths worldwide. Because current treatments for advanced non-small cell lung cancer (NSCLC), the most prevalent lung cancer histological subtype, show limited efficacy, screening for tumor-associated biomarkers using bioinformatics reflects the hope to improve early diagnosis and prognosis assessment. In our study, a Gene Expression Omnibus dataset was analyzed to identify genes with prognostic significance in NSCLC. Upon c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 39 publications
(37 reference statements)
0
22
0
Order By: Relevance
“…Differences of the expression levels of CXCRs between AML patients and normal tissues were obtained from the GEPIA website ( ). the Gene Expression Profiling Interactive Analysis server (GEPIA) is a newly developed interactive web server ( 17 ) for analyzing the RNA sequencing expression data of thousands of tumor and normal samples from the TCGA and the GTEx projects using a standard processing pipeline ( 18 ). Since AML samples from TCGA database were all tumor samples, GEPIA matches normal samples from the GTEs database.…”
Section: Methodsmentioning
confidence: 99%
“…Differences of the expression levels of CXCRs between AML patients and normal tissues were obtained from the GEPIA website ( ). the Gene Expression Profiling Interactive Analysis server (GEPIA) is a newly developed interactive web server ( 17 ) for analyzing the RNA sequencing expression data of thousands of tumor and normal samples from the TCGA and the GTEx projects using a standard processing pipeline ( 18 ). Since AML samples from TCGA database were all tumor samples, GEPIA matches normal samples from the GTEs database.…”
Section: Methodsmentioning
confidence: 99%
“…The tests were performed according to the previous methods. 38 The primer sequences were listed as follows: Human CD147-Forward: 5′-GACGACCAGTGGGGAGAGTA-3′ Human CD147-Reverse: 5′-GGCCTTGTCCTCAGAGTCAG-3′ Monkey CD147-Forward: 5′-GGCTCGAAGACACTCCTCAC-3′ Monkey CD147-Reverse: 5′-GAGTACTCTCCCCCGAGGTC-3′ Human/monkey ACE2-Forward: 5′-GTGCACAAAGGTGACAATGG-3′ Human/monkey ACE2-Reverse: 5′-GGCTGCAGAAAGTGACATGA-3′ Human/monkey GAPDH-Forward: 5′-GCACCGTCAAGGCTGAGA AC-3′…”
Section: Rna Extraction and Real-time Pcr Analysismentioning
confidence: 99%
“…It has been shown that multiple genes can be used as potential biomarkers for the diagnosis and prognosis of lung cancer ( 54 , 55 ). However, to the best of our knowledge, there are currently limited studies available on the effective molecular diagnostic markers of LUAD and LUSC.…”
Section: Discussionmentioning
confidence: 99%